Analisis Dampak Kemajuan IPTEK Terhadap Pelaksanaan Pembelajaran Daring di Sekolah Dasar - Addely Damayanti Noer; Perdana, Parisca Indra; Harsiwi, Nova Estu (Pendagogia: Jurnal Pendidikan Dasar, 2025)
The Covid-19 pandemic has caused major changes, one of which is the education system. Changes in the education system have made it difficult for students to receive materials, especially students at the elementary school level. Digitalization, which is characterized by technological developments, provides many conveniences and learning media is also growing. This study aims to analyze the development of online learning media during and after the pandemic. Sources are taken from books, articles and interview results to obtain the information needed in order to achieve research goals. A more varied learning platform is the best alternative to provide a non-monotonous learning atmosphere for learners